Bibliometric Analysis: Interactive Learning Model Assisted by Digital Technology - Anjani, Dewi Maulidah Nur; Supatmi (Buletin Edukasi Indonesia, 2024)
The world of education is evolving rapidly alongside technological advancements, demanding educators to adapt to the changing times and leverage technology. Consequently, various teaching models have emerged, prompting an analysis to evaluate their effectiveness. This study employs meta-analysis, drawing data from multiple scholarly journals, to assess existing teaching models. Such models are indispensable in education, particularly in school settings. Notable examples include ASSURE, POE, ARIAS, PBL, virtual labs, and technology-based approaches such as online platforms like WhatsApp, Google Classroom, and YouTube applications. Each teaching model exhibits distinct characteristics, allowing educators to integrate or select them according to specific needs. This analysis aims to empower educators to make informed decisions regarding the adoption and customization of teaching models.